A review of the Oriental grassland leafhopper genus Platyretus Melichar (Hemiptera: Cicadellidae: Deltocephalinae) - Viraktamath, C. A.; Webb, M. D.; Dai, Wu; Zhang, Yalin (Zootaxa, 2008)
The genus Platyretus is redescribed and a key to the five included species is given. The new species described are Platyeretus brevipenis Wu & Zhang sp. nov. (from China), P. gangeticus Viraktamath & Webb sp. nov. (from north India and China), P. javanicus Viraktamath & Webb sp. nov. (from Java) and P. sudindicus Viraktamath & Webb sp. nov. (from south India). The type species P. marginatus Melichar and the new species are described and illustrated along with a key to recognize them. Platyretus pseudocinctus Heller & Linnavuori and Platyretus himalayanus Distant are not treated as they are considered as not belonging in this genus. The former probably belongs to an undescribed deltocephaline genus and the latter is a member of Evacanthinae.